The Influence of the ‘Makassar Kota Makan Enak’ City Branding on City Image and Tourists’ Visiting Decisions to Makassar City - Nurjannah Nurjannah; Sabran Laori; Muh Yahya; Vinny Corylitha Sarapang; Nur Tria Iriani (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - Makassar City possesses diverse tourism potential, including natural, cultural, artificial, and culinary attractions. To strengthen its tourism competitiveness, the Makassar City Government introduced the city branding slogan “Makassar Kota Makan Enak” (Makassar: The City of Delicious Food) in 2023. This study aims to examine the effect of city branding on city image and tourists’ visit decisions to Makassar City. The topic is important because an effective city branding strategy can shape positive perceptions of a destination and encourage tourist visits. Design/methodology/approach - This study employed a quantitative research approach. Data were collected through questionnaires distributed to tourists originating from outside Makassar City. The collected data were analyzed using SPSS version 31 to examine the relationships among City Branding, City Image, and Visit Decision variables. Finding/Results - The results indicate that City Branding has a significant positive effect on City Image. Furthermore, City Branding significantly influences tourists’ Visit Decisions, while City Image also has a significant positive effect on Visit Decisions. These findings suggest that the branding initiative successfully enhances tourists’ perceptions of Makassar and contributes to their decision-making process when choosing the city as a travel destination. Originality/Value - This study provides empirical evidence regarding the role of city branding in influencing tourist behavior through the formation of a positive city image. The findings imply that “Makassar Kota Makan Enak” is an effective branding strategy that not only strengthens the city’s image but also increases tourists’ intention and decision to visit Makassar City. The main contribution of this research is demonstrating that city image serves as an important mechanism through which city branding affects tourists’ visit decisions.